2017
DOI: 10.1002/srin.201600509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solidification Pressure on Compactness Degree of 19Cr14Mn0.9N High Nitrogen Steel Using CAFE Method

Abstract: The cellular automaton‐finite element (CAFE) model is used to simulate solidification structures of 19Cr14Mn0.9N high nitrogen steel under different solidification pressures. The effect of solidification pressure on model parameters is firstly investigated. After validation, this model is used to clarify the effect of solidification pressure on compactness degree with number of grains and primary dendrite arm spacing (λ1). The results show that increasing solidification pressure from 0.5 to 1.2 MPa exhibits a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The increment of pressure can speed up the reaction rate, improve the cooling rate, refine the solidification structure and eliminate the solidification defects, etc. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In addition, increasing pressure can effectively refine carbides to alleviate the negative effect. Li 16) increases pressure and higher solidification pressure is beneficial to reduce the volume fraction of M 6 C. Therefore, it is worth exploring a new method to improve quality of H13 ingot using the pressurized metallurgy technology.…”
Section: Effect Of Pressure On Dendrite Structure and Characteristics Of Carbides During Solidification Process Of H13 Die Steel Ingotmentioning
confidence: 99%
See 1 more Smart Citation
“…The increment of pressure can speed up the reaction rate, improve the cooling rate, refine the solidification structure and eliminate the solidification defects, etc. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In addition, increasing pressure can effectively refine carbides to alleviate the negative effect. Li 16) increases pressure and higher solidification pressure is beneficial to reduce the volume fraction of M 6 C. Therefore, it is worth exploring a new method to improve quality of H13 ingot using the pressurized metallurgy technology.…”
Section: Effect Of Pressure On Dendrite Structure and Characteristics Of Carbides During Solidification Process Of H13 Die Steel Ingotmentioning
confidence: 99%
“…where, ρ is the density of steel, kg/m 3 ; λ is the heat conductivity coefficient, W/(m•K); C P is the specific heat, J/(kg•K). The latent heat of solidification is obtained by enthalpy method, which is as follow: 28)…”
Section: Mathematical Modelmentioning
confidence: 99%
“…More specifically, the cellular automaton-finite element (CAFE) model, by virtue of its explicit physical mechanism, high simulation precision, and other advantages, has been widely applied in the simulation of solidification structure [4][5][6][7][8]. Based on the CAFE model, the simulation of solidification structure provides powerful theoretical support and practical guidance for optimizing the process of continuous casting slabs [9,10], square billets [11][12][13], round billets [14][15][16][17], and other types of steel.…”
Section: Introductionmentioning
confidence: 99%
“…16,19,20) Gavrilova et al 20) has proposed that a small increment of pressure (several MPa) can significantly increase heat transfer coefficient and refine the casting structure of HNSs. Zhu et al, 26) using CAFE method to investigate the effect pressure on compactness degree of high nitrogen steel, has concluded that higher solidification pressure is favourable to increase the number of grains of the whole ingot and reduces the primary dendrite arm spacing of central equiaxed. However, there is a lack of experimental study on relationship between solidification pressure and dendritic structure.…”
Section: Introductionmentioning
confidence: 99%